Lymphocyte active immunotherapy for unexplained recurrent spontaneous abortion (Bangladesh Journal of Pharmacology, 2018)
This study is to evaluate the curative effect of lymphocyte active immune treatment for unexplained recurrent spontaneous abortion. Fourteen randomized controlled trials of 994 subjects were included. Blocking antibody positive rate of patients who experienced a new pregnancy showed significant differences between immunotherapy and placebo. Moreover, live birth rate among paternal or third-party donor lymphocytes and placebo groups had significant difference [RR= 1.63, 95% CI (1.38-1.92), p＜0.05]. Trial sequential analysis showed that the Z-curve crosses the trial sequential monitoring boundaries, confirming that the clinical benefit of active immunotherapy was significant. Subgroup analysis suggests that immunotherapy with lymphocytes might be more effective for primary recurrent spontaneous abortion than for secondary recurrent miscarriage. Taken together, women with primary recurrent spontaneous abortion who are negative for blocking antibody prior to treatment seemed most likely to obtain a potential beneficial effect of lymphocyte active immunotherapy, but not secondary recurrent spontaneous abortion.